Diritto ed esercito. Profili dell’epoca tardoantica - Atti Convegno Parma, 22 e 23 novembre 2018 - Puliatti, Salvatore (Cultura giuridica e diritto vivente, 2020)
[Law and Army. Late Antiquity Profiles. Parma, 22 and 23 November 2018] The essays collected in the present volume reproduce the contributions presented at the Conference Law and Army. Late Antiquity Profiles, held in Parma on 22 and 23 November 2018. They allow the reader to understand more closely the status of the military, the impact of their role in legal life and their link with civilian life.